Neurofilament Light Chain Related to Longitudinal Decline in Frontotemporal Lobar Degeneration. Issue 2 (April 2021) - Zhang, Jiasi Vicky; Irwin, David J.; Blennow, Kaj; Zetterberg, Henrik; Lee, Edward B.; Shaw, Leslie M.; Rascovsky, Katya; Massimo, Lauren; McMillan, Corey T.; Chen-Plotkin, Alice; Elman, Lauren; Lee, Virginia M.-Y.; et al.
Abstract : Objective: Accurate diagnosis and prognosis of frontotemporal lobar degeneration (FTLD) during life is an urgent concern in the context of emerging disease-modifying treatment trials. Few CSF markers have been validated longitudinally in patients with known pathology, and we hypothesized that CSF neurofilament light chain (NfL) would be associated with longitudinal cognitive decline in patients with known FTLD-TAR DNA binding protein ~43kD (TDP) pathology. Methods: This case-control study evaluated CSF NfL, total tau, phosphorylated tau, and β-amyloid1-42 in patients with known FTLD-tau or FTLD-TDP pathology (n = 50) and healthy controls (n = 65) and an extended cohort of clinically diagnosed patients with likely FTLD-tau or FTLD-TDP (n = 148). Regression analyses related CSF analytes to longitudinal cognitive decline (follow-up ∼1 year), controlling for demographic variables and core AD CSF analytes. Results: In FTLD-TDP with known pathology, CSF NfL is significantly elevated compared with controls and significantly associated with longitudinal decline on specific executive and language measures, after controlling for age, disease duration, and core AD CSF analytes. Similar findings are found in the extended cohort, also including clinically identified likely FTLD-TDP. Although CSF NfL is elevated in FTLD-tau compared with controls, the association between NfL and longitudinal cognitive decline is limited to executive measures. Conclusion: CSF NfL is associated with longitudinal clinical decline in relevant cognitive domains in patients with FTLD-TDP after controlling for demographic factors and core AD CSF analytes and may also be related to longitudinal decline in executive functioning in FTLD-tau.